Parotid gland carcinoma masquerading as an aural polyp - Subha, Sethu Thakachy; Abu Bakar, Saraiza; Prepageran, Narayanan (Mashhad University of Medical Sciences, 2019)
Introduction: Parotid gland squamous cell carcinoma is an uncommon aggressive neoplasm with poor prognosis. Aural polyps are usually the presenting features of chronic suppurative otitis media, tuberculous otitis media, and adenoma or carcinoma. The malignant aural polyp is very rare. Parotid gland carcinoma masquerading as an aural polyp has rarely been described in the literature. Case Report: We report a case study of parotid squamous cell carcinoma in a 29-year-old male masquerading as an ear polyp. Conclusion: Parotid gland primary squamous cell carcinoma is a rapidly advancing neoplasm which carries poor prognosis despite multimodality treatment. Diligent clinical and histopathological evaluation is imperative to discriminate this rare aggressive disease from the metastatic and other primary cancers of the parotid. A high index of suspicion is crucial in refractory aural polyps to arrive at early diagnosis.